Factors associated with levels of health-related quality of life in elderly women: secondary data analysis of the Korea National Health and Nutrition Examination Survey 2019 - Miseon Son (Korean Society of Women Health Nursing, 2022)
Purpose The purpose of this study was to investigate factors related to the levels of health-related quality of life (HRQoL) in elderly women based on Wilson and Cleary's HRQoL model. Methods This study analyzed data from the eighth Korea National Health and Nutrition Examination Survey 2019 on 868 women over the age of 65 years. Based on the HRQoL model, parameters were categorized as personal, environmental, and physiological characteristics; symptom status; functional status; and perception of health status. The data were analyzed by quantile regression. Results The overall level of HRQoL was 0.87. Factors related to HRQoL in the 10% quantile were higher education level, higher economic status, economic activity, more walking days, fewer diseases, lower stress, less activity limitation, and higher perceived health status. Factors related to the 25% quantile of HRQoL were more walking days, fewer diseases, less activity limitation, and higher perceived health status. Factors related to the 50% quantile were age, economic activity, more walking days, fewer disease, lower stress, less activity limitation, and higher perceived health status. Factors related to the 75% quantile of HRQoL were smoking, more walking days, fewer diseases, lower stress, less activity limitation, and higher perceived health status. Conclusion While differing parameters were identified according to the level of HRQoL of elderly women in Korea, there were five common factors. Interventions that focus on increasing walking, mitigating diseases, stress, and activity limitations, and improving perceived health status can improve HRQoL.